The Hubungan Tingkat Literasi Kesehatan Digital dengan Perilaku Higienitas Diri pada Anak Sekolah - Nurul Amaliyah; Indah Wiranda; Lintang Sari (Buletin Keslingmas, 2026)
Digital health literacy is a person's ability to search, understand, evaluate, and utilize available health information, which, for children at the elementary school level, is very important to help them read and understand health materials to form good hygiene habits, because the inability to choose accurate health information can have a negative impact. The purpose of this study is to determine the relationship between the level of digital health literacy and personal hygiene behavior in fifth and sixth-grade students at SDN XY East Pontianak. The type of research used is quantitative with a descriptive correlational design. Data collection was carried out using questionnaires on 50 fifth and sixth-grade students at SDN XY East Pontianak. The sampling technique used was proportional random sampling. Data analysis was carried out using the Gamma statistical test to determine the relationship between the level of digital health literacy and personal hygiene behavior. The results of the analysis showed a significant relationship between the level of digital health literacy and personal hygiene behavior in elementary school children (p-value <0.05) with a Gamma coefficient value of 1.000. This indicates that the better a child's digital health literacy, the better their personal hygiene behaviors in daily life. The study concluded that there is a significant relationship between digital health literacy and personal hygiene behaviors in elementary school children. Children with good digital health literacy tend to have better personal hygiene behaviors.